Comparative study between behavioral patterns of sibling of children suffering from chronic diseases and healthy children - Sami'ei; S. Parsa-Yekta; Z. Mehran; A. Masouri; S. (Tehran University of Medical Sciences, 2003)
This research is a descriptive-analytical study conducted with the aim of examining and comparing adjusted behaviors of children (brothers and sisters) suffering from a chronic disease, referred to treatment centers with the siblings of the healthy children of the same age, in Tehran. The research sample was a group of 300 children along with a pair of parents. They were divided into groups of 150 siblings suffering from a chronic disease and 150 siblings who were healthy. For sample-taking of the children suffering from chronic disease parents of the children referring to hospitals or hospitalized in wards, who had the required qualifications were also studied through simple random selection. In order to select healthy children and their parents, the parents of the children referring to specified treatment centers for receiving medication and clinical treatment were selected as the control group, through the simple random sampling method. The basis of research comprised of a questionnaire comprising of two parts. The 1st part consisted of demographic particulars and the 2nd part constituted the form of questions put to the child's parents, whose form was prepared on the basis of the standardized child behavior checklist in accordance with Achen Bach's parents' report. The form consisted of two parts: one concerning social merit (6 questions on activities, social relations and studying performance of the child); while the other related to behavioral problems of the child (102 questions in relation to social problems, anti-social behavior, aggressive behavior, difficulty in concentration, physical complaints, anxiety, depression, isolation disorder in thinking, sexual problems and miscellaneous matters). The results in relation to the research objectives point out that there is by p<0.001 and p< 0.005 and in a sensible manner, the behavioral problems of the siblings suffering from a chronic disease as compared with healthy siblings are more and their social merit is less.